TAFSIR AHKAM DALAM PERDAGANGAN SUATU TELAAH HUKUM ISLAM - ramadani, ramadani (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2022)
Abstractthe political law of sharia banking, it will be imagined in the mind that the law is something weak. That is, law is in a position as an object of politics, and politics as a subject that influences the law. What is the form of politics in banking and what is the scope of politics and banking, while the conclusion is that various factors influence the formation of Islamic banking law in Indonesia, namely, ideological, religious, political, social, and cultural factors. As for the advice given in building a country that is safe, peaceful, and peaceful, we should help each other in the economic development of our country. AbstractDalam cakupan luaspun seperti internasional, perdagangan menjadi sebuah penghubung hubungan antar suatu Negara. Perdagangan yang dilakukan dengan baik tentu akan berakibat baik pula baik bagi seorang pedagang maupun bagi pembelinya, itu lah sebabnya di dalam agamapun menjelaskan mengenai perdagangan, yang tertuang dalam kitab suci Al-Quran, adapun rumusan masalah adalah apa yang dimaksud dengan perdagangan, Apa dalil beserta tafsirannya dalam Al-quran mengenai perdagangan